1993
DOI: 10.1042/bj2940575
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a B-type esterase involved in insecticide resistance from the mosquito Culex quinquefasciatus

Abstract: The enzyme, esterase B2, involved in insecticide resistance has been purified and characterized from the mosquito Culex quinquefasciatus. The monomeric enzyme has an M(r) of 62000 and a pI of 5.0. This enzyme is compared with the esterase A2 previously characterized [Ketterman, Jayawardena and Hemingway (1992) Biochem. J. 287, 355-360]. The kinetic constants for interaction with several insecticides indicate, as for the esterase A2, that the B2 enzyme has a role in resistance. The rates and affinities of bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 23 publications
4
71
0
Order By: Relevance
“…Amplification of a single esterase, coded for by the estβ1" gene, was first shown in the Californian TEM-R strain of mosquito [18]. Immunological and molecular studies have since suggested that the estβ1", estβ1# and estβ2" genes were originally alleles of the same locus [10,20,21]. More recently, cloning of the estα2" cDNA has enabled comparison of the coding regions of the estα and estβ esterase genes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of a single esterase, coded for by the estβ1" gene, was first shown in the Californian TEM-R strain of mosquito [18]. Immunological and molecular studies have since suggested that the estβ1", estβ1# and estβ2" genes were originally alleles of the same locus [10,20,21]. More recently, cloning of the estα2" cDNA has enabled comparison of the coding regions of the estα and estβ esterase genes [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 (11,12). The electrophoretic mobility on native PAGE of the Pel SS-purified Est␣ was reproducibly faster than that of the resistant Est␣2 1 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The Pel SS Est␤1 3 K m for pNPA was significantly higher than those of the resistant Est␤2 previously observed for Pel RR (140.8 Ϯ 5.24 M), Dar91 (85.41 Ϯ 3.94 M), and Tanga85 (90.11 Ϯ 6.49 M) (12,17). In contrast, the Pel SS Est␣3 and Est␤1 3 esterase pNPH K m values are not significantly different from those previously reported for Est␣2 1 and Est␤2 1 (17).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations